Social Physics Comes to the Workplace. - Davis, Joseph E. (Hedgehog Review)
The article exposes some of the more frighteningly intrusive data-based monitoring tools and techniques that now effectively bring Auguste Comte's dream of social physics to our shop floors, offices, and cubicles. It mentions that in the quantified workplace workers themselves will be no less active than management as tools for shaping an ever more productive and harmonious team.